2021
DOI: 10.1186/s40249-021-00848-x
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization road map for neglected tropical diseases 2021–2030: implications for onchocerciasis elimination programs

Abstract: In its new roadmap for neglected tropical diseases, the World Health Organization proposes three important strategic shifts: (i) Stronger accountability which shifting from process to impact indicators; (ii) Intensified cross-cutting approaches; and (iii) Stronger country ownership. In this paper we discuss the implementation of these three strategies in the setting of a high onchocerciasis disease burden in South Sudan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Ivermectin mass drug administration (MDA) has been used for decades in programs for onchocerciasis and lymphatic filariasis (LF) elimination, demonstrating an excellent safety profile (except where Loa loa is co-endemic), and high effectiveness against the target filarial parasites [ 6 , 7 ]. Ivermectin MDA is also increasingly being adopted for scabies control [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ivermectin mass drug administration (MDA) has been used for decades in programs for onchocerciasis and lymphatic filariasis (LF) elimination, demonstrating an excellent safety profile (except where Loa loa is co-endemic), and high effectiveness against the target filarial parasites [ 6 , 7 ]. Ivermectin MDA is also increasingly being adopted for scabies control [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…NS was documented mainly in South Sudan, Uganda, and Tanzania. However, it was also reported in other Onchocerciasis endemic regions [1,7,9,16,17]. In fact, Ov infection might induce a broad spectrum of pathologies, termed together Onchocerciasis.…”
Section: Introductionmentioning
confidence: 81%
“…The affected children experience a complete and permanent stunting of growth and mental handicap [ 2 , 3 , 4 , 7 , 8 ]. While NS is still enigmatic, it is strongly associated with the parasitic worm OV [ 1 , 5 , 8 , 9 , 15 , 16 , 17 , 18 , 53 ]. Recently, it was shown that autoimmunity might drive the pathology of this disease [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These chronic, disabling, and sometimes disfiguring diseases historically receive less attention compared to other diseases occurring in the same regions [3] . The World Health Organization (WHO) African region bears the greatest burden of NTDs, accounting for 40% of global cases as of 2022, excluding chagas disease [4] , and with the most countries experiencing a high NTD burden per million inhabitants [5] .…”
Section: Introductionmentioning
confidence: 99%